Tutuh Nya' Tiop, Akal Nya' Midop, Local Wisdom and Cultural Sustainability in Education - Paramitha, Elizabeth; Sutrisno, Hery; Bintang, Pianus; Waruwu, Marinu; Halida, Halida (Jurnal Pendidikan Sosiologi dan Humaniora, 2026)
Ka' Jubata," the phrase "Tutuh Nya' Tiop, Akal Nya' Midop" is originate from the Dayak ethnic in Sanggau Regency. It is occasionally used as an opening greeting before delivering a speech. It carries the meaning “Even if our clothes are made of bark, our minds must stay alive.” This moral philosophy and life values of the Dayak people emphasized the importance of simplicity and wisdom. This research aim is to explore the philosophy's meaning which embodies the local wisdom and its role in promoting cultural sustainability in education. The objective is to analyze the philosophy on educational practices. The scope of this research covers educational sets within the society that actively embrace this wisdom. This research is a qualitative research design using ethnographic methods. Data were collected through participatory observation, in-depth interviews with cultural leaders, and documentation of cultural artifacts. Analytical instruments include thematic analysis and content categorization to interpret meanings and applications of the philosophy in educational activities. The findings reveal that philosophy embodies values of simplicity, intellectual vitality, and cultural resilience, reflecting the community’s philosophy wisdom and knowledge guide human life despite material limitations. These values can serve as the foundation for culturally responsive education that promotes moral integrity and sustainable cultural preservation. The study concludes that integrating “Tutuh nya’ tiop, akal nya’ midop” into educational practice strengthens local identity and supports the continuity of Dayak moral philosophy in modern learning contexts.